Effect of Behavior on the Utilization of KIA Books in Pregnant Women at the Lawe Sumur Public Public Health Center, Lawe Sumur Sub District, Aceh Tenggara District - Wahyuni Wahyuni; Khoirotun Najihah; Marcella Chatarina (LLDIKTI Wilayah 1, 2021)
The KIA Handbook is a simple but effective means of communicating and recording the health of pregnant women as an information, education, and communication. According to data from Lawe Sumur Aceh Tenggara Public Health Center, there were 118 pregnant women where they had received the KIA book. The purpose of this study is to determine how they use the KIA books for the pregnant women at Lawe Sumur Public Public Health Center, Lawe Sumur Sub District, Aceh Tenggara District. This type of research is an analytic survey with a cross sectional design. Research location at Public Public Health Center Lawe Sumur. This study was held on October 2020. The research population is all of the pregnant woman reach 118 woman in Lawe Sumur Public Health Center territory. The sampling technique with cluster sampling for 54 people. The Data Analysis by using univariat, bivariat using chu-square test, and multivariate using multiple logistic regression test. The results of the research with logistic regression showed the p-value for the knowledge variable (p = 0.008) with the Exp (B) = 9,100, the attitude (p = 0.021) with the Exp (B) value = 0.021 and the action (p = 0.187) with the Exp (B) = 2.979. The conclusion of this study is that there is a significant effect of knowledge and attitudes on the use of the KIA handbook and there is no significant effect on the use of the KIA handbook. It is advisable for pregnant women to comply with ANC visits and to use the KIA handbook.